2015
DOI: 10.12657/steciana.018.008
|View full text |Cite
|
Sign up to set email alerts
|

Nature valuation of plant communities in the Zagórów polder including water content parameters

Abstract: ABSTRACT. Geobotanical studies conducted in spring in 2011-2012 in the Zagórów polder washland, covered by the ecological restoration programme, provided assessment of current nature value of plant communities and indicated potential directions of their further transformations as a result of changes in habitat water content levels. Based on the analyses of 77 relevés of 50-100 m 2 each, prepared following the Braun-Blanquet method, water levels were assessed by phytoindication using moisture indicator values (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…In intensively managed Arrhenatheretum elatioris meadows, the average FUV was 7.9 with approximately 80% of grass cover. By contrast, in extensively used meadows with a high nature conservation value and herb cover, the FUV is 6.8 with 60% of grass cover (Kryszak et al, 2010). A positive correlation between biomass production and the FUV has been found…”
Section: Effect Of Experiments On Hay Quality and Quantitymentioning
confidence: 85%
“…In intensively managed Arrhenatheretum elatioris meadows, the average FUV was 7.9 with approximately 80% of grass cover. By contrast, in extensively used meadows with a high nature conservation value and herb cover, the FUV is 6.8 with 60% of grass cover (Kryszak et al, 2010). A positive correlation between biomass production and the FUV has been found…”
Section: Effect Of Experiments On Hay Quality and Quantitymentioning
confidence: 85%
“…In the analyzed decade, low precipitation and reduced flows in the Supraśl River were found on the site, limiting the irrigation of adjacent meadows (Kiryluk, 2019). Research by Kryszak et al (2011) also showed that the factor determining the floristic diversity of plant com- munities in drainage canals and ditches are water relations, depending e.g. on a current state of land reclamation devices and their maintenance.…”
Section: Discussionmentioning
confidence: 97%
“…The occurrence of drainage ditches in protected areas may interfere with the performance of their irrigation and drainage functions (Grzywna and Szajda, 2008;Kiryluk, 2007). Conservation measures in ditches and canals, progressive eutrophication of waters contribute to the formation of anthropogenic succession in plant communities occurring there (Kryszak et al, 2011). Proper selection of the type and timing of maintenance works on the bottom and the slopes of the watercourse may reduce changes in the composition of communities and the number of taxa (Bondar-Nowakowska et al, 1997;Przybyła et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation